Comparative Sensitivity and Specificity of the 7SL sRNA Diagnostic Test for Animal Trypanosomiasis - Contreras Garcia, Maria; Walshe, Emily; Steketee, Pieter C.; Paxton, Edith; Lopez-Vidal, Javier; Pearce, Michael C.; Matthews, Keith R.; Ezzahra-Akki, Fatima; Evans, Alec; Fairlie-Clark, Karen; Matthews, Jacqueline B.; Grey, Finn; et al. (Frontiers in Veterinary Science, 2022)
Animal trypanosomiasis (AT) is a significant livestock disease, affecting millions of animals across Sub-Saharan Africa, Central and South America, and Asia, and is caused by the protozoan parasites Trypanosoma brucei, Trypanosoma vivax, and Trypanosoma congolense, with the largest economic impact in cattle. There is over-reliance on presumptive chemotherapy due to inadequate existing diagnostic tests, highlighting the need for improved AT diagnostics. A small RNA species, the 7SL sRNA is excreted/secreted by trypanosomes in infected animals, and has been previously shown to reliably diagnose active infection. We sought to explore key properties of 7SL sRNA rt-qPCR assays; namely, assessing the potential for cross-reaction with the widespread and benign Trypanosoma theileri, directly comparing assay performance against currently available diagnostic methods, quantitatively assessing specificity and sensitivity, and assessing the rate of decay of 7SL sRNA post-treatment. Results showed that the 7SL sRNA rt-qPCR assays specific for T. brucei, T. vivax, and T. congolense performed better than microscopy and DNA PCR in detecting infection. The 7SL sRNA signal was undetectable or significantly reduced by 96-hours post treatment; at 1× curative dose there was no detectable signal in 5/5 cattle infected with T. congolense, and in 3/5 cattle infected with T. vivax, with the signal being reduced 14,630-fold in the remaining two T. vivax cattle. Additionally, the assays did not cross-react with T. theileri. Finally, by using a large panel of validated infected and uninfected samples, the species-specific assays are shown to be highly sensitive and specific by receiver operating characteristic (ROC) analysis, with 100% sensitivity (95% CI, 96.44-100%) and 100% specificity (95% CI, 96.53-100%), 96.73% (95% CI, 95.54-99.96%) and 99.19% specificity (95% CI, 92.58-99.60%), and 93.42% (95% CI, 85.51-97.16% %) and 82.43% specificity (95% CI, 72.23-89.44% %) for the T. brucei, T. congolense and T. vivax assays, respectively, under the conditions used. These findings indicate that the 7SL sRNA has many attributes that would be required for a potential diagnostic marker of AT: no cross-reaction with T. theileri, high specificity and sensitivity, early infection detection, continued signal even in the absence of detectable parasitaemia in blood, and clear discrimination between infected and treated animals.